Bonus versus penalty: how robust are the effects of contract framing? - De Quidt, Jonathan; Fallucchi, Francesco; Kölle, Felix; Nosenzo, Daniele; Quercia, Simone (Springer, 2017)
We study the relative effectiveness of contracts that are framed either in terms of bonuses or penalties. In one set of treatments subjects know at the time of effort provision whether they have achieved the bonus / avoided the penalty. In another set of treatments subjects only learn the success of their performance at the end of the task. We fail to observe a contract framing effect in either condition: effort provision is statistically indistinguishable under bonus and penalty contracts.